Influence of the mold inhibitor on productivity and functional activity of broiler chicken’s liver - A. A. Baeva; L. A. Vityuk; I. R. Tletseruk; N. V. Lyashenko (Новые технологии, 2017)
During the experiment broiler chickens were the object of the research. The purpose of the study was to study the effect of different doses of the Oxy-Nile mold inhibitor in rations with an increased content of B1 aflatoxin on the utility-beneficial qualities and functional activity of the liver of broiler chickens. In the course of the experiment, it was established that to optimize utility indicators and functional activity of the liver in the feed of broiler chickens with a tolerant concentration of B1 aflatoxin , it is recommended to include the Oxy-Nile mold inhibitor in the amount of 600 g / t of feed.